Determination of naloxegol in human biological matrices - Li, Yan; Hoffmann, Mark; Severin, Paul (Bioanalysis, 2017)
Naloxegol is an oral peripherally acting μ-opioid receptor antagonist approved for the treatment of opioid-induced constipation. Sensitive, robust, bioanalytical methods were required to quantitate naloxegol in human biological matrices as part of the clinical development program. Analytical plasma samples were prepared using Solid Phase Extraction (SPE) coupled with concentration. The method's linearity was established at 0.1-50 ng/ml with up to 100-fold dilution. Urine samples were analyzed directly postdilution; dialysate samples were extracted by supported liquid extraction. Sensitive liquid chromatography/mass spectrometry (LC-MS/MS) assays were developed and validated, and demonstrated acceptable precision, accuracy and selectivity for naloxegol in the appropriate matrices. Methods for quantifying naloxegol in human biological matrices have been successfully validated.